Retrospective study on 48-h fluid balance and outcome in mechanically ventilated critically ill children - Namita Ravikumar; Ramachandran Rameshkumar; Ponnarmeni Satheesh; Subramanian Mahadevan (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: There is limited data on the outcome of mechanically ventilated critically ill children in low- and middle-income countries. The aim was to study the association of fluid balance in mechanically ventilated critically ill children and outcomes. Methodology: This retrospective study was conducted in an academic hospital's pediatric intensive care unit (PICU) from January 2015 to December 2016. Children aged 1 month to 12 years ventilated for more than 24 h with 48-h fluid balance were included in the study. Patients were divided into ≤10% and >10% fluid overload (FO) groups. The primary outcome was all-cause PICU mortality. The secondary outcomes were the durations of mechanical ventilation, PICU and hospital stay; organ failure; and extubation failure. Results: A total of 107 patients (23 in >10%-FO and 84 in ≤10%-FO groups) were enrolled. The median (interquartile range) age and pediatric risk of mortality III score were similar in both groups (12, 7-36 months vs. 11, 3-32 months; P = 0.37; and 16, 12-20 vs. 15, 12-18; P = 0.71, respectively). The most common indication for ventilation was disordered control of breathing (55% vs. 42%) followed by respiratory pathology (30% vs. 39%). In >10%-FO group, higher proportion of patients had acute respiratory distress syndrome (13 [56%] vs. 28 [35%], P = 0.06) and acute kidney injury (15 [65%] vs. 37 [44%)], P = 0.07), of which a significant number required renal replacement therapy (10 [43%] vs. 15 [17%], P = 0.01). More patients had septic shock in >10%-FO group (13 [56%] vs. 27 [32%], P = 0.03). There was no significant difference in all-cause PICU mortality in >10%-FO groups (13 [57%]) as compared to ≤10%-FO group (32 [38%]) (relative risk = 1.2, 95% confidence interval [CI]: 1.0-1.5, P = 0.11; and adjusted hazard ratio = 1.52, 95% CI: 0.78-2.97, P = 0.22). No differences were noted in other outcome variables. Conclusion: There was no significant difference in mortality and morbidity noted in 10% FO cutoff in critically ill mechanically ventilated children. A larger sample size, preferably a multicentric study, is warranted.